Self-Efficacy and Self-Directed Learning Profiles of High-Achieving Students - Budiartiningsih, Rahmita; Suryawati, Evi; Siregar, Syarifah Nur; Meiwanda, Geovani; Harfal, Zaldi (Jurnal Pendidikan Humaniora, 2023)
This study aimed to explore the profiles of Self-Efficacy (SE) and Self-Directed Learning (SDL) among students at Universitas Riau, providing insights into their potential for academic and non-academic achievement. The findings indicate that 31% of the outstanding students were male, while 69% were female. The average SE scores were 4.36 for male students and 4.31 for female students, while the SDL scores were 4.20 for males and 4.18 for females. The results show no statistically significant differences between male and female students in terms of SE and SDL, suggesting that both genders have equal opportunities for success in academic and non-academic pursuits.